Electrical Conductivity of S-Acetylthiocholine Halides and Perchlorate in Ethanol at 40 ºC - H. El-Hammamy, Nasr; M. El-Kashlan, Howaida; M. Moharem, Heba (Asian Journal of Chemistry, 2012)
The conductance of S-acetylthiocholine halides and perchlorate has been measured in ethanol at 40 ºC. The data were analyzed using the Fuoss-Onsager equation for 1:1 associated electrolytes and the characteristic functions, Lº (conductance at infinite dilution), a0 (contact distance) and KA (association constant) were computed. KA values were analyzed on the basis of the solvent separated-ion pair model.